Optical Parallel Quaternary Signed Digit Multiplier For Large Scale Two-Dimensional Array Using Digit-Decomposition Plane Representation - Al-Saffar, Alaa A. W. (Iraqi Journal for Electrical and Electronic Engineering, 2007)
An optical parallel quaternary signed digit (QSD) two-dimensional array multiplier based on digit-decomposition (DDP) representation and duplication-shifting-superimposing algorithm is proposed in this paper. The multiplication operation is done in three steps; one for partial products generation and the other two steps perform accumulation to find the DDP planes of the final result array. QSD multiplication and addition rules are used to obtain a newly derived equations which are suitable for easy optical implementation using basic optical tools. Finally, simulation results are presented to validate the successful of the multiplication operation.